APLIKASI TEPUNG TAPIOKA DAN GAPLEK TERMODIFIKASI FISIK DALAM PEMBUATAN MI LETHEK - Nuri Arum Anugrahati; Elsie Carista (Universitas Pelita Harapan, 2020)
Lethek noodles are Yogyakarta's special food made from a mixture of cassava flour and tapioca flour. The application of tapioca flour and cassava chips as a result of the physical modification of the multi-cycle cooling-heating has not been carried out in the making of lethek noodles. The aim of this study was to apply physical modified tapioca and cassava flour and guar gum in the making of lethek noodles and determine their effects on the physical characteristics of lethek noodles. Physical modification of tapioca and cassava flour is done by heating-cooling 2 and 3 cycles. The heating process is carried out using an autoclave at 121ºC for 30 minutes, then followed by cooling at 4ºC for 24 hours. The study was designed with a Completely Randomized Design with variations in the ratio of tapioca flour and cassava chips modified (25:75, 50:50, and 75:25) and the concentration factor of guar gum (0%; 0.5%; 1%; 1.5 %). The results showed that the amylose content of physically modified cassava flour was higher (72.04%) than physically modified cassava flour (49.15%). The more modification of tapioca flour added, the lower cooking loss and the higher hardness of lethek noodles. The higher concentration of guar gum, the lower cooking loss and hardness of lethek noodles. Therefore, it can be stated that physical modified tapioca and gaplek flour can be applied in the making of lethek noodles and the best lethek noodles was made from the ratio of physical modified tapioca and cassava flour 75:25 and guar gum concentration of 1%.